The Effect of Implant Length and Diameter on Stress Distribution around Single Implant Placement in 3D Posterior Mandibular FE Model Directly Constructed Form In Vivo CT - Shinya Akikazu; Ishida Yoshiki; Miura Daisuke; Shinya Akiyoshi (MDPI, 2022)
A three-dimensional (3D) finite element (FE) model of the mandibular bone was created from 3D X-ray CT scan images of a live human subject. Simulating the clinical situation of implant therapy at the mandibular first molar, virtual extraction of the tooth was performed at the 3D FE mandibular model, and 12 different implant diameters and lengths were virtually inserted in order to carry out a mechanical analysis. (1) High stress concentration was found at the surfaces of the buccal and lingual peri-implant bone adjacent to the sides of the neck in all the implants. (2) The greatest stress value was approximately 6.0 MPa with implant diameter of 3.8 mm, approx. 4.5 MPa with implant diameter of 4.3 mm, and approx. 3.2 MPa with implant diameter of 6.0 mm. (3) The stress on the peri-implant bone was found to decrease with increasing length and mainly in diameter of the implant.